AB0681 Can Conventional and Non-Conventional Cardiovascular Markers Identify Different Types of Cardiovascular Involvement in Ankylosing Spondylitis and Psoriatic Arthritis. (15th July 2016) - Atzeni, F.; Gianturco, L.; Bongiovanni, S.; Boccassini, L.; Sarzi-Puttini, P.; Turiel, M.
Abstract : Background: Cardiovascular (CV) mortality is increased in patients with ankylosing spondylitis (AS) and psoriatric arthritis (PsA) but there are very few publications concerning CV morbidity. Furthermore, the findings of a number of studies indicate that AS and PsA are associated with different CV manifestations. Objectives: The aim of the study was to use conventional and unconventional CV markers such as common carotid IMT (ccIMT), carotid pulse wave velocity (PWV), ejection fraction (EF) and global longitudinal strain (GLS) assessed by means of speckle tracking echocardiography (STE) to identify the different types of CV involvement in AS and PsA. Methods: The study involved 30 outpatients satisfying the New York diagnostic criteria for AS (14 males and 16 females; mean age 53.07±10.73 years; mean disease duration 5.03±4.06 years), and 30 outpatients satisfying the CASPAR criteria for PsA (15 males and 15 females; mean age 54.27±9.63; mean disease duration 5.73±4.07 years), matched in terms of age, gender and other anthropometric characteristics. None of the participants had smoked cigarettes during the previous ten years or showed any signs or symptoms of CV disease, pulmonary involvement, or any other complication. All of the patients were treated with DMARDs and anti-inflammatory drugs, but none had received any biological or steroid therapy at baseline. They were therefore normal in terms of basal ECG tracking, blood pressure (BP) values and glyco-lipid profiles (hypertension, dyslipidemia, diabetes and hyperuricemia were exclusion criteria). All of the patients underwent a clinical and standard echocardiographic examination, a carotid ultrasound study (including IMT and PWV assessment), and STE of the left ventricle (LV) using commercial QLAB Philips software. Results: There were no differences between the AS and PsA groups in terms of EF and traditional echocardiographic parameters such as ccIMT (right: median right 0.64 mm, IQR 0.48–0.78 mm vs 0.64 mm, IQR 0.50–0.79 mm; p =0.07; and left: 0.64 mm, IQR 0.49–0.80 mm vs 0.64 mm, IQR 0.50–0.80 mm; p =0.08). However, PWV was higher in the PsA group (right: median 7.82, m/sec:, IQR 7.05–8.45, m/sec vs 7.08, m/sec, IQR 6.92–7.92, m/sec; p =0.04; and left: median 7.80 m/sec, IQR 6.99–8.41 m/sec vs 7.07 m/sec, IQR 6.93–7.92 m/sec; p=0.04), and GLS was lower in the AS group (median 19.83, IQR 16.00–24.40 vs 20.03, IQR 18.12–24.82; p=0.02). Conclusions: The study findings show that our AS patients had impaired GLS in comparison with those with PsA, thus suggesting a myocardial alteration, and our PsA patients had higher PWV values than the AS patients, thus indicating endothelial dysfunction. There were no differences in ccIMT, EF or other conventional echocardiographic indexes between the two groups, but these findings suggest that AS and PsA patients are affected by different types of CV alteration, and the importance of identifying them in order to prevent CV events. Disclosure of Interest: None declared